Correction: 3D printed nervous system on a chip. Issue 10 (19th April 2016) - Johnson, Blake N.; Lancaster, Karen Z.; Hogue, Ian B.; Meng, Fanben; Kong, Yong Lin; Enquist, Lynn W.; McAlpine, Michael C.
Abstract : Correction for '3D printed nervous system on a chip' by Blake N. Johnson et al., Lab Chip, 2016, 16, 1393–1400.